IMPLEMENTASI NILAI KEBANGSAAN DALAM PENGABDIAN MASYARAKAT DI DESA OGOTUA MELALUI KEGIATAN LOMBA 17 AGUSTUS HUT RI KE-80 - Moh Wahyu; Irawati Irawati; Fadila M. Iksan; Santriana Santriana; Saiful Saiful; Amanda Octaviani; Evayulianti Evayulianti; Muh. Khaerul Ummah BK; Ayu Lestari; Muhammad Iqbal; Masrin Gafar; Nursifa Nursifa; Eka Liow; Abdul Wahid Safar (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The community service activity through the implementation of the Independence Day competitions in Ogotua Village was carried out as an effort to foster nationalism while strengthening social cohesion in commemorating the 80th Anniversary of Indonesia’s Independence. The background of this initiative lies in the concern over the declining patriotic spirit among the younger generation, influenced by globalization and the lack of awareness of national values. Therefore, the Independence Day competitions serve as a strategic medium to revive unity, sportsmanship, and solidarity. The program consisted of several stages, including committee formation, technical meetings, equipment preparation, competition implementation, and a closing ceremony with prize distribution. The results showed a high level of enthusiasm from the community as well as full support from village officials. The competitions—such as mini soccer, women’s volleyball, fun walks, gymnastics, and marching—successfully created an atmosphere of togetherness and joy while strengthening patriotic values. Thus, this activity not only served as annual entertainment but also as a character-building medium and reinforcement of nationalism that should be preserved in the future.